Influence of chatbots on the export of information technology services in Asia: bibliographic review period 2019-2022 - Agustín Vásquez Tarrillo, Renzo (2024)
This study focuses on analyzing the influence of chatbot implementation on the export of information technology services in China, South Korea, Hong Kong during the period 2019-2022.The methodology employed a systematic review of scientific literature, making the development mostly a qualitative descriptive design.Additionally, 30 research articles were selected to analyze how personalization of interactions with clients, self-service, and the collection of feedback in chatbots influence the exportation of information technology services.The findings indicate that the implementation of chatbots has emerged as a critical factor in optimizing the processes of exporting information technology services in a highly competitive and digitized market.